2020
DOI: 10.1007/s11356-020-08971-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water quality variation on fish assemblages in an anthropogenically impacted tropical estuary, Colombian Pacific

Abstract: In tropical estuaries, fish diversity varies spatially and temporally due to behavioral processes such as reproductive migrations, predator avoidance, and foraging, which are affected by water quality. Eutrophication is one of the main factors affecting water quality in estuaries. The objective of this study was to determine variation in fish assemblage explained by fluctuating water quality in the Buenaventura Bay. Fish were captured using artisanal trawl nets during the wet, dry, and transitional seasons at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 66 publications
5
27
0
14
Order By: Relevance
“…Referente al pH, se evidenció una correspondencia significativa de forma negativa con los crustáceos, lo cual se puede relacionar con la cantidad de sustancias disueltas, especialmente nutrientes, los cuales tienen efectos sobre peces y macroinvertebrados estuarinos, afectando su abundancia y disponibilidad como presas (Day et al, 1989;Duque et al, 2020). También se ha encontrado que el océano Pacífico colombiano tiene una tendencia a largo plazo de disminuir el pH en los sectores marino costeros (Rojas y Pabón, 2015), relacionada con factores como la absorción de CO 2 presente en la atmosfera por los océanos.…”
Section: Influencia De Variables Fisicoquímicas En Los Hábitos Tróficosunclassified
See 1 more Smart Citation
“…Referente al pH, se evidenció una correspondencia significativa de forma negativa con los crustáceos, lo cual se puede relacionar con la cantidad de sustancias disueltas, especialmente nutrientes, los cuales tienen efectos sobre peces y macroinvertebrados estuarinos, afectando su abundancia y disponibilidad como presas (Day et al, 1989;Duque et al, 2020). También se ha encontrado que el océano Pacífico colombiano tiene una tendencia a largo plazo de disminuir el pH en los sectores marino costeros (Rojas y Pabón, 2015), relacionada con factores como la absorción de CO 2 presente en la atmosfera por los océanos.…”
Section: Influencia De Variables Fisicoquímicas En Los Hábitos Tróficosunclassified
“…Turning to pH, a clear and significant negative correspondence was found between this variable and crustaceans, which may be associated with the quantity of dissolved substances -especially nutrients -that affect estuarine fish and macroinvertebrates, affecting their abundance and their availability as prey (Day et al, 1989;Duque et al, 2020). It has also been found that the Colombian Pacific is experiencing a long-term tendency to reduced pH levels in coastal areas (Rojas y Pabón, 2015), a phenomenon related to factors such as the absorption of atmospheric CO 2 by the oceans.…”
Section: Influence Of Physico-chemical Variables On Trophic Habitsmentioning
confidence: 99%
“…En 2010 entre 4,8 y 12,7 millones de toneladas métricas de residuos plásticos llegaron a los océanos y se estima que 5 trillones de piezas plásticas están flotando actualmente en el mar (Wessel et al, 2016). La Bahía de Buenaventura es un estuario vulnerable a este tipo de contaminación y sus comunidades de bentos, macroinvertebrados y peces (Gamboa et al, 2018;Martinez et al, 2019;Duque et al, 2020;Molina et al, 2020) podrían ser afectadas por la ingestión de microplásticos (Tafurt, 2020). El objetivo de la presente investigación fue determinar la distribución, densidad, y tipo feeders, macroinvertebrates, fish, reptiles, and mammals are found among the ingestion-vulnerable organisms, which ingest them either directly or through ingesting other organisms (Guzzetti et al, 2018;Reed et al, 2018).…”
Section: Introductionunclassified
“…Between 4.8 and 12.7 million metric tons of plastic waste arrived in the ocean in 2010, and it is estimated that 5 trillion plastic pieces are currently floating on the sea (Wessel et al, 2016). Buenaventura Bay is a vulnerable estuary to this type of pollutant, and their communities of benthos, macroinvertebrates, and fish (Gamboa et al, 2018;Martinez et al, 2019;Duque et al, 2020;Molina et al, 2020) could be affected by ingestion of microplastics (Tafurt, 2020). The objective of this research was to determine the distribution, density, and type of microplastics in sediments in the Buenaventura Bay estuary, Colombian Pacific, comparing two sites of the estuary in three climatic seasons in years 2015 and 2019.…”
Section: Introductionmentioning
confidence: 99%
“…As in many countries of the world, an important product in the human diet in Russia is fish, its biodiversity in all water bodies is associated with geographical, biotic, and abiotic factors [10] whose ratio and changes affect the number of fish in certain populations. First, the ecological safety of fish is associated with water quality, since all pollutants migrate through food chains with its participation.…”
Section: Introductionmentioning
confidence: 99%